Cover Image. (3rd August 2020) - Lazarus, Carole; Weiss, Pierre; El Gueddari, Loubna; Mauconduit, Franck; Massire, Aurélien; Ripart, Mathilde; Vignaud, Alexandre; Ciuciu, Philippe
Abstract : The cover image is based on the Research Article 3D variable‐density SPARKLING trajectories for high‐resolution T2*‐weighted magnetic resonance imaging by Philippe Ciuciu, Alexandre Vignaud, Carole Lazarus et al., https://doi.org/10.1002/nbm.4349